Simplified SVPWM Technique for Ripple-Free Voltage and Current Control in Flying Capacitor of Five-Level Hybrid ANPC Converters - Hakami, Samer Saleh; Lee, Kyo Beum (2023 IEEE Conference on Energy Conversion, CENCON 2023, 2023)
This paper introduces a simplified space vector pulse width modulation (SVPWM) technique aimed at achieving ripple-free voltage and current control in the flying capacitor of five-level hybrid active neutral point clamped (ANPC) converters. The existing phase-shift SVPWM (PS-SVPWM) technique employed in the five-level hybrid ANPC converter exhibits good performance and natural balancing capabilities, but suffers from significant voltage and current ripples in the flying capacitor, leading to system performance degradation and reliability issues. In this study, the proposed technique addresses these challenges by carefully selecting the switching states of the converter to effectively eliminate voltage and current ripples. This approach simplifies the computation and implementation of SVPWM, resulting in reduced computational burden and enhanced real-time control capabilities. Extensive simulation results demonstrate the effectiveness of the technique in achieving ripple-free control, thereby improving the overall converter performance and enhancing system reliability. The proposed simplified SVPWM technique offers a promising solution for the practical implementation of five-level hybrid ANPC converters in various high-power applications.
Keywords: Active neutral point clamped; Five-level hybrid active neutral-point-clamped converter; Flying capacitor; Flying capacitor ripple-free; Modulation techniques; Neutral-point clamped converters; Ripple-free; Simplified space vector pulse width modulation; Space vector pulse width modulation; Voltage ripples; five-level hybrid active neutral-point-clamped (HANPC) converters; flying capacitor ripple-free; simplified space vector pulse width modulation (SVPWM); voltage and current control